A continuing agenda for gender: the role of the IGU Commission on gender and geography. Issue 7 (3rd July 2017) - Huang, Shirlena; Monk, Janice; Droogleever Fortuijn, Joos; Garcia-Ramon, Maria Dolors; Momsen, Janet Henshall
Abstract: In examining the development of the International Geographical Union's (IGU) Commission on Gender and Geography over the last three decades, we first highlight the advances made to establish visibility for gender studies within the IGU and create structures for more inclusive feminist geographies across national, disciplinary and other borders. Given that many of the early and most widely-known advances were largely within Anglophone contexts, we then discuss the ongoing challenges and possibilities for advancement faced by feminist geographers who teach, research, and write on gender in other locations. While some of these challenges (such as a continued lack of recognition for gender studies, paternalistic hierarchies, and specific government regimes) are country-specific, others are related to broader issues of neoliberalism and corporatization, and inequities in academic publishing. Clearly, continued efforts are needed to strengthen the agenda for gender to promote more inclusive histories, practices and processes of gender/feminist geography in research, teaching and application in the international arena.